Protective multifunctional fibrous systems based on natural fibers and metal oxide nanoparticles - Araújo, Joana Carolina Carvalho (2021)
In recent years, an unprecedented increase in the development of products and technologies to protect the human being has been observed. Now, more than ever, the world population is exposed to several threats, harmful to their well-being and health. Chemical and biological hazardous agents stand out as one of the biggest threats, not only for the military forces, but also for the civilians. Consequently, it’s essential to develop personal protective systems that are able to protect their user, not only passively, but actively, being able to detect, adsorb, degrade and decontaminate pesticides, pollutants, microorganisms and most importantly: chemical/biological warfare agents. One recent strategy for the development of active fibrous structures with improved functions and new properties is their functionalization with nanoparticles (NPs), especially metal oxides. Although their known effectiveness in the decomposition of harmful agents, the NPs could also include other functionalities in the same structure using low quantities of material, without adding extra weight, which is of huge importance for a soldier in the battlefield. The use of natural fibers as the substrate is also very interesting, since this material is a much sustainable alternative when compared to synthetic ones, also providing excellent properties.